2016
DOI: 10.1007/978-3-319-48496-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Scan-to-BIM and FEM for the Documentation and Analysis of Heritage Timber Roof Structures

Abstract: Abstract. Current heritage analysis applications and documentation techniques for timber roof structures rely on manual measurements to provide the spatial data. Major simplifications are made to document these structures efficiently. However, these simplified geometric models provide less reliable results. Therefore, the need exists for more realistic models. Additionally, the exchangeability of information between varying parties is paramount. Hence, the construction elements should be defined in a Building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
(12 reference statements)
0
37
0
3
Order By: Relevance
“…Existen, además, muchos otros estudios realizados en el contexto de la metodología BIM aplicada a edificios históricos [4,5,7,11,13,18,19,21,24], pero todos son trabajos sobre un edificio específico y para un estilo arquitectónico particular. Ninguno de ellos ofrece una solución general, lo cual es lógico dado el amplio rango de posibilidades que se pueden encontrar cuando se trata de edificios históricos.…”
Section: Revisión Bibliográfica Pasado Y Presente Del Hbimunclassified
“…Existen, además, muchos otros estudios realizados en el contexto de la metodología BIM aplicada a edificios históricos [4,5,7,11,13,18,19,21,24], pero todos son trabajos sobre un edificio específico y para un estilo arquitectónico particular. Ninguno de ellos ofrece una solución general, lo cual es lógico dado el amplio rango de posibilidades que se pueden encontrar cuando se trata de edificios históricos.…”
Section: Revisión Bibliográfica Pasado Y Presente Del Hbimunclassified
“…Bassier et al [13] compared the complex geometric models, considering the data acquisition, the modelling, and the structural analysis of timber roof structures defined in a Building Information Modelling to a traditional wire-frame model, and showed that the BIM complex models provide a more reliable result in terms of geometry and structural behaviour.…”
Section: Heritage Documentationmentioning
confidence: 99%
“…Therefore, they can simultaneously automate the element segmentation and parametric representation procedure in BIM environment by specific functions. Bassier et al (2016) noted the important role of BIM from scan data to structural analysis model for heritage timber roof structures. They utilized BIM technique to connect the geometry model (SolidWorks ScanTO3D) and structural analysis (ANSYS) (Figure 1).…”
Section: Revit Api Developmentmentioning
confidence: 99%
“…The obtained beam system is linear wire-frame model, and it is increasingly accepted to transfer it to the solid model in the BIM environment. Compared to the traditional wire-frame model, the BIM solid model provides not only definite relationship and variable parameters descripting the beam elements, but also more reality results in terms of geometry and structure behavior (Bassier, 2016).…”
Section: Total Station Data Sourcementioning
confidence: 99%